ISOLATION AND GENETIC DETECTION OF MORAXELLA BOVIS FROM BOVINE KERATOCONJUNCTIVITIS IN BASRAH CITY - & et al., Hadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to determine the most sensitive isolation procedures and evaluate the genetic diversity of Moraxella bovis because there are large number of pathogenic bacteria and several other infectious agents such as virus and Mycoplasma have been isolated from the eyes infected with infectious bovine keratoconjunctivitis (IBK). This study included examination of (40) eye swabs, from cows from different ages and regions in Basrah city showed clinical signs of an ocular infection. The isolated bacteria that obtained in pure cultures were non-motile, catalase and oxidase positive, and a clear zone of β-hemolytic colonies were produced on blood agar. According to the growth characteristics, morphology, staining and biochemical tests, the isolated bacteria were identified  initially as Moraxella spp., the genetic diversity among Moraxella spp. was assessed by 16S rRNA and sequencing as M. bovis. The study has also indicated that the isolates of M. bovis were resistant to tetracycline, chloramphenicol and erythromycin, However, they were sensitive to penicillin and gentamicin and has an intermediate sensitivity to streptomycin. This study concluded that PCR techniques and sequencing were verified to be most accurate tools to indicate the genetic diversity between Moraxella spp. in bovine keratoconjunctivitis.